The representation of the rural exodus in Spanish cinema (1900-2020): evolution, causes and territorial consequences - Antonio Martinez-Puche; Salvador Martínez Puche; Francisco Javier García Delgado; Xavier Amat Montesinos (Investigaciones Geográficas)
Rural depopulation has been a constant feature of contemporary Spanish history and has been amply studied from the perspective of geography. Recently, however, there has been considerable media attention given to the consequences of internal migration. Behind the alarming demographic statistics lies a nexus of processes which have been reflected in the cinema since its beginning. This paper explores these processes at work in the rural sending environment and receiving urban destination through an analysis of six representative Spanish films. The fictional representation through film of a complex reality provides insights into the internal and contextual keys to understanding the phenomenon of ‘empty Spain’ or ‘hollowed-out Spain’. The films illustrate the persistence of two conflicting ideas (the rural and urban), divergence about what constitutes development and the quality of life, and the processes leading to ‘demotanasia’.